Odpowiedzi

2009-11-20T11:03:06+01:00
1.
m=3+√5 i n=1-2√5.
m+n= 3+√5+1-2√5=4-√5
m-n=3+√5-1+2√5=3+3√5
m×n=(3+√5)(1-2√5)=3-6√5+√5-2×5=3-5√5-10=-7-5√5
m÷n=(3+√5)÷(1-2√5)=(3+√5)(1+√5)÷(1-2√5)(1+2√5)=
=(3+√5+3√5+5)÷(1-4×5)=(8+4√5)÷(-19)

2.
a) (x-3)(x+3) + 5x = x(x-2)
x²-9+5x=x²-2x
x²-9+5x-x²+2x=0
7x-9=0
7x=9
x=9/7

b) (y-1)² > y(y+4) - 3y tam chyba zamiast x powinno byc y
y²-2y+1>y²+4y-3y
y²-2y+1-y²-4y+3y>0
-3y+1>0
1>3y
y<⅓

Najlepsza Odpowiedź!
2009-11-20T11:03:19+01:00
M=3+√5 i n=1-2√5
m+n=(3+√5) +(1-2√5)=3+√5+1-2√5=4-√5
m-n= (3+√5) -(1-2√5)=3+√5-1+2√5=2+3√5
m×n= (3+√5)* (1-2√5)=3+√5-6√5-2*5=-7-5√5
m÷n=(3+√5)/ (1-2√5)=(3+√5)*(1+2√5)/ (1-2√5)*(1+2√5)=(3+√5+6√5+10)/(1-4*5)=(13+7√5)/-19

a) (x-3)(x+3) + 5x = x(x-2)
x²-9+5x=x²-2x
x²-x²+5x+2x=9
7x=9
x=9/7

b) chyba zamiast x powinno być y
(y-1)² > y(y+4) - 3y
y²-2y+1>y²+4y-3y
y²-y²-2y-4y+3y>-1
-3y>-1
y<1/3
  • adaz
  • Początkujący
2009-11-20T11:16:41+01:00
(x-3)(x+3)+5x=x(x-2)
X2 +3x - 3x - 9 +5x -x(x-2) = O
x2 - 9 +5x -x2 + 2x =0
7x=9
x=7/9

(y-1)2>y(x+4)-3y
y2-2y+1 > yx + 4y - 3y
y2 - 2y +1 - yx - 4y +3y >0
y2 - 3y + 1 -yx>0

....??
chyba tresc lekko pomylona w tym 2?